O apoiador caipira: o desafio/arte de articular redes regionais a partir de territórios/desejos singulares - Yahn, Pedro Ivo Freitas De Carvalho; Yasui, Silvio (UNESP, 2014)
Considering the experience taken from the institutional support given by the Humanization’s Brazilian Policy in three health’s regions in São Paulo State, Brazil, this text intends to expose some problems refering to the articulation process of other health’s regional networks mainly composed by cities with less than twenty thousands inhabitants. By problematizing the articulation of inlad health’s networks it is put on the agenda the process of descentraliztion and the interfederaditive relations emphasizing the political and institutional aspects that goes through and modulates these relations, mainly in the small cities. Thus, we are questioning the ways how the current health policies are implemented in these territories and the way how they are articulated, having as a goal the challenge of the process’ ascendance and transversality.

Através de la experiencia del apoyo institucional de la Política Brasileña de Humanización en tres regiones de salud del interior del Estado de São Paulo, Brasil, el presente texto se propone exponer algunas problematizaciones referentes al proceso de articulación de mallas regionales de salud en regiones compuestas mayoritariamente por municipios con menos de vente mil habitantes. Al problematizar la articulación de mallas de salud en regiones interioranas se pone en la pauta del proceso de descentralización y las relaciones inter-federativas enfatizando los aspectos políticos institucionales que penetran y modulan esta relación, principalmente en los municipios de pequeño porte. Por consiguiente, ponemos en cuestión los modos como las políticas de salud actuales llegan a estos territorios y el modo cómo estas mallas están siendo articuladas, teniendo como dirección el desafío de la ascendencia y transversalidad del proceso.

Por meio da experiência do apoio institucional da Política Nacional de Humanização em três regiões de saúde do interior do estado de São Paulo, Brasil, o presente texto visa expor algumas problematizações referentes ao processo de articulação de redes regionais de saúde em regiões compostas majoritariamente por municípios com menos de vinte mil habitantes. Ao problematizar a articulação de redes de saúde em regiões interioranas, coloca-se na pauta o processo de descentralização e as relações interfederativas enfatizando os aspectos político-institucionais que atravessam e modulam essas relações, principalmente nos municípios de pequeno porte. Assim sendo, colocamos em questão os modos como as atuais políticas de saúde chegam a esses territórios e o modo como essas redes estão sendo articuladas, tendo como norte o desafio da ascendência e transversalidade do processo.
The “caipira” supporter: the challange/art of articulating regional networks from single territories/wishes
El apoyador “caipira”: el desafío/arte de articular mallas regionales por medio de territorios/deseos singulares
Keywords: Institutional support; Health’s regional networks; Interfederative relations; Ascendance; Transversality; Apoio institucional; Redes regionais de saúde; Relação interfederativa; Ascendência; Transversalidade